Development of knee function after hamstring lengthening as a part of multilevel surgery in children with spastic diplegia: a long-term outcome study - Dreher, Thomas; Vegvari, Dóra; Wolf, Sebastian Immanuel; Geisbüsch, Andreas; Gantz, Simone; Wenz, Wolfram; Braatz, Frank (The journal of bone & joint surgery. A, American volume, 2012)
Background: Hamstring lengthening commonly is performed for the treatment of flexed knee gait in patients with spastic diplegic cerebral palsy. Satisfactory short-term results after hamstring lengthening have been demonstrated in various studies. However, evidence for the effectiveness of hamstring lengthening to correct flexed knee gait is scant because of small and inhomogeneous case series, different surgical techniques, and short follow-up. Methods: The long-term results for thirty-nine patients with spastic diplegia and flexed knee gait who were managed with intramuscular hamstring lengthening as a part of multilevel surgery are presented. Standardized three-dimensional gait analyses and clinical examinations were performed for all patients preoperatively and at one, three, and six to twelve years postoperatively. Results: Significant improvements in kinematic parameters and the popliteal angle were noted at short-term follow-up (p < 0.01), supporting the results of previous studies. Long-term results showed significant deterioration of minimum knee flexion in stance and the popliteal angle (p < 0.01), whereas the improvements in the Gross Motor Function Classification System and Gillette Gait Index were maintained. This recurrence of flexed knee gait is partial and measurable. Increased pelvic tilt was found in 49% of the limbs postoperatively, which may represent one factor leading to recurrence of flexed knee gait. Genu recurvatum was seen in eighteen patients (twenty-seven limbs; 35%) one year postoperatively, especially in the patients with a jump knee gait pattern preoperatively. At long-term follow-up, genu recurvatum resolved in many limbs, but 12% of the limbs showed residual genu recurvatum, indicating that overcorrection represents a problem following hamstring lengthening. Conclusions: The results of the present study are crucial for the prognosis of knee function after hamstring lengthening as a part of multilevel surgery. Recurrence and possible overcorrection should be considered in treatment planning. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 11.12.2018